“ANALYTICAL INVESTIGATION OF THE STORE ENVIRONMENT AND SPONTANEOUS PURCHASE. THE CHANGING DYNAMICS OF CONSUMER BEHAVOUR IN ISTANBUL DEPARTMENTAL STORES”,TURKEY - Abbas, Dr. Manzir; Sheikh, Sadaf; Cengel, Dr. Ozgur (The journal of contemporary issues in business and government, 2021)
We intended to figure out the main factors that were affecting consumers buying and established the model for unplanned buying, for the case of departmental stores located in Lahore. We included a sample with different (independent) buying behaviour, emotions of customers, promotion & advertisement, physical environment and price of products variables. The objective was set to examine the leading factors influencing customers to buy in departmental stores (MM Migro's, A-101, Bim and Śuck) of Istanbul, Turkey. The survey approach was taken in this study through a proper sampling design using convenience sampling with sample size 250 were used in the study. Overall the result was derived to the conclusion by using the SPSS software and find valid reliability for the variables. We found correlation between different variable to check the relationship and regression model to check model significant. Finally, this study can propose valuable policy implications.